Phytochemical Profiling, Optimization of Extraction Methods, and Biological Activities of Buxus sempervirens Leaves - Muskan Bhardwaj; Garima Garg; Brij Mohan Sharma (Natural Resources for Human Health, 2026)
The leaves of Buxus sempervirens contain numerous phytochemical compounds such as alkaloids, flavonoids, and tannins that possess significant medicinal properties and have industrial uses as well. This study was conducted to identify optimum conditions for extracting bioactive compounds from the plant and to assess their biological activities. In the current study, bioactive compounds were extracted from the leaves of B. sempervirens using the Soxhlet extraction method employing ethanol and methanol as solvents. For the phytochemical profiling, TLC, GC-MS, and HPLC analyses were used. It was found that methanolic extraction produced the highest yields of alkaloids and flavonoids. Preliminary phytochemical analysis confirmed the presence of tannins, saponins, and steroids. Furthermore, the extracts demonstrated a strong antioxidant, anti-inflammatory, and antimicrobial activity. Thus, optimization of the extraction process proved helpful in increasing the yield and improving biological activity of the phytochemical compounds obtained. As a result, this study showed B. sempervirens to be a rich source of various bioactive compounds that might find application in the field of pharmaceuticals, nutraceuticals, and cosmetics industry.